Translation of culture-specific items in foreign publicity texts : a case study of a bite of China II episode 1 & 2 - Huang, Jingjing (Nanyang Technological University, 2020)
In cross-cultural communication, different cultures are involved where common knowledge may be quite limited. This causes obstacles in understanding of another linguistic expression. In other words, the translation of messages is not only on the linguistic aspect, more importantly, it is a cultural transmittance. The most obvious differences in cultures exist in the culture specific items (CSIs), which leads to complexities in transferring the semantic meanings and cultural concepts from one culture to another. The particular text type of foreign publicity requires the translation to be accurate, objective and communicative, which poses more challenges in CSI translation. While the TV documentary A Bite of China produced by China Central Television (CCTV) receives great popularity both in China and overseas, the subtitle function as foreign publicity texts are worthy analyzed. This paper uses the Chinese and English subtitles in A Bite of China Season II Episode 1 & 2 as corpus to analyze the translation strategy for CSIs. The taxonomy of CSIs proposed by Nida is applied to analyze the CSI classification and suitable translation strategies are explored with the goal to promote effective foreign publicity. Suggestions for improvement are given in the hope that the quality of foreign publicity translation can be improved and awareness towards the significance of the translation activity can be raised.